Hb A2-Pistoia [δ89(F5)Ser→Asn, HBD: c.269G>a]: a Novel Mutation on the δ-Globin Gene in an Italian Child. (2nd September 2020) - Guastini, Adriana; Rizzi, Leonardo; Santoni, Fabiano; Mogni, Massimo; Maffei, Massimo; Vinci, Santina; Barberio, Giuseppina; Coviello, Domenico; Ivaldi, Giovanni
Abstract: We describe a new hemoglobin (Hb) variant, found in a 6-year-old Italian male living in Pistoia, Italy. An abnormal pattern compatible with a Hb A2 variant was observed on capillary electrophoresis (CE); direct sequencing revealed a transition at codon 89 of the δ gene ( HBD : c.269G>A) changing serine into asparagine. The variant was also identified as Hb A2 -Pistoia according to the traditional nomenclature and no other globin defect was present. The observation and description of this Hb A2 variant contributes to the number and heterogeneity of mutations of the δ-globin gene in the Mediterranean Area.